Highly crystalline lithium chloride-intercalated graphitic carbon nitride hollow nanotubes for effective lead removal. Issue 11 (3rd October 2019) - Zhou, Ying; Liao, Changzhong; Fan, Yiang; Ma, Shengshou; Su, Minhua; Zhou, Zhengyuan; Chan, Ting-Shan; Lu, Ying-Rui; Shih, Kaimin
Abstract : The intercalation of chloride in the interstitial space of highly crystalline graphitic carbon nitride provides effective binding sites for Pb(ii ). Abstract : The functional groups and intercalated ions in the structure of graphitic carbon nitrides can be tailored to attain excellent physiochemical properties for environmental remediation. In this work, a highly crystallized lithium chloride-intercalated graphitic carbon nitride (LiCl-CN) material was fabricated through well-controlled molten salt synthesis. The as-prepared materials presented hollow tube morphology with tetragonal geometric configurations. Batch adsorption experiments showed that the LiCl-intercalated graphitic carbon nitride (LiCl-CN-4 h) exhibited excellent lead cation (Pb(ii )) adsorption capacity (172.41 mg g −1 ) at pH 5.5. Thermodynamic parameters revealed the endothermic and spontaneous nature of Pb(ii ) adsorption on LiCl-CN-4 h, and the kinetics results demonstrated that chemisorption dominated the adsorption process. X-ray diffraction analysis indicated that the intercalation of Cl and Li can lead to a larger interlayer spacing between carbon nitride layers. An X-ray photoelectron spectroscopy and X-ray absorption spectroscopy investigation further elucidated the chemical binding sites of Cl–Pb in the lattice of LiCl-CN, indicating the intercalation of Cl − ions contributed to the large improvement of Pb(ii ) adsorption capacity in g-C3 N4 materials. The experimental results demonstrate that this is a facile and environmentally friendly strategy for synthesizing highly crystalline LiCl-CN with hollow tube morphology, and that the material showed promise for efficient Pb(ii ) removal in environmental remediation applications.